Editorial to TOWARDS THE MAELSTROM - Jaqueline Pierazzo; Luciano Moreira (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
Editorial to thematic section by the guest editors.